Neurological soft signs in recent-onset schizophrenia: Focus on the cerebellum - Hirjak, Dusan; Wolf, Robert Christian; Kubera, Katharina Maria; Stieltjes, Bram; Maier-Hein, Klaus H.; Thomann, Philipp (Progress in neuro-psychopharmacology & biological psychiatry, 2015)
Background - Previous structural neuroimaging studies linked cerebellar deficits to neurological soft signs (NSS) in schizophrenia. However, no studies employed a methodology specifically designed to assess cerebellar morphology. In this study, we evaluated the relationship between NSS levels and abnormalities of the human cerebellum in patients with recent-onset schizophrenia and healthy individuals using an exclusive cerebellar atlas. - Methods - A group of 26 patients with recent-onset schizophrenia and 26 healthy controls were included. All participants underwent a high-resolution T1-weighted MRI scan on a 3 Tesla scanner. We used a voxel-based morphometry (VBM) approach utilizing the Spatially Unbiased Infratentorial (SUIT) toolbox to provide an optimized and fine-grained exploration of cerebellar structural alterations associated with NSS. - Results - Compared with healthy controls, patients had significantly smaller cerebellar volumes for both hemispheres. In the patients' group, we identified a significant negative correlation between NSS levels and gray matter volume in the left lobule VI and the right lobule VIIa, corrected for multiple comparisons. Further, NSS performance was significantly associated with white matter volume in the left midbrain and corpus medullare and the right lobule VIIa. In contrast, no significant associations between NSS scores and cerebellar subregions in healthy subjects arose. - Conclusion - Our results demonstrate the benefits of SUIT when investigating cerebellar correlates of NSS. These results support the view that distinct parts of sensorimotor and cognitive cerebellum play an important role in the pathogenesis of NSS in schizophrenia.
Gesehen am 03.09.2020